Optimalisasi Proses Bioremediasi Secara In Situ Pada Lahan Tercemar Pestisida Kelompok Mankozeb - Setiyo Yohanes; Made S Utama; Wayan Tika; IBP. Gunadnya (Jurnal Teknik Industri, 2011)
Compost as an organic fertilizer could improve the physical, chemical, and biological characteristics of the soil in a certain way so that soil mineral was available for plant. The special aim of this research was to optimize the bioremediation process for degradation of pesticide residues at Bedugul Agro-tourism so that organic farming system will be sustainable. Based on C/N, and pH, it could be concluded that better solution for bioremediation of pesticide residue problem was by giving mixed-compost in horticulture cultivation. Deviation of pH in bioremediation process was 0.22, and pH in-situ bioremediation process was between 6.9 and 7.12 or neutral pH. In this condition micro-organism would be effective in degrading pesticide residue. Bioremediation process on pesticide residue of Ditane M-45 at horticulture cultivation deploy with 1.2 g/l/20 m2, 2.4 g/l/20 m2, and 3.6 g/l/20 m2 spraying dosages took place perfectly, which was showed by parameters on development of micro-organism population and the amount of pesticide residues. Pesticide residue of each spraying dosages was 0.25–1.7% at 35 days or this values were under 0.003 ppm.